2021
DOI: 10.3390/coatings11101212
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Active Edible Coating Based on Sodium Caseinate, Chitosan and Oregano Essential Oil Reinforced with Silica Particles and Its Application on Panela Cheese

Abstract: Active edible films and coatings incorporating antimicrobial agents such as essential oils are studied to improve the shelf-life of fresh foods. The aim of this work was to study a mixture of sodium caseinate-chitosan (SC:CH), added with mesoporous silica nanoparticles filled with oregano essential oil (MSN-OEO), to produce an active edible coating for Panela cheese and to evaluate its properties during refrigerated storage for 15 days. The OEO was extracted by hydrodistillation and was incorporated into the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The decrease in pH is likely due to the organic acids, such as lactic acid, produced by the increasing bacterial population. Coated cheeses have a higher pH, probably due to partial inhibition of lactic acid bacteria 40 . The high pH value in samples containing probiotics may be due to the coating treatment, which acts as an encapsulated substance that preserves the stability of the bacteria 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in pH is likely due to the organic acids, such as lactic acid, produced by the increasing bacterial population. Coated cheeses have a higher pH, probably due to partial inhibition of lactic acid bacteria 40 . The high pH value in samples containing probiotics may be due to the coating treatment, which acts as an encapsulated substance that preserves the stability of the bacteria 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Coated cheeses have a higher pH, probably due to partial inhibition of lactic acid bacteria. 40 The high pH value in samples containing probiotics may be due to the coating treatment, which acts as an encapsulated substance that preserves the stability of the bacteria. 16 Additionally, the higher pH of the coated samples may be due to the reduced migration of acids through the coating.…”
Section: Characteristics Of Cheese Slicesmentioning
confidence: 99%
“…Total soluble contents of the ricotta cheese were determined by using refractometer according to the method as explained in AOAC 2016. Milk and whey sample’s moisture content was analyzed by using moisture analyzer by following the procedure as explained by Ríos-de-Benito et al (2021). Protein contents of fresh milk and cheese whey was determined through Kjeldhal method as described in AOAC (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Ricotta cheese was coated by following the method as explained by Ríos-de-Benito et al, 2021. Using a spray gun, the coating was applied to samples of Panela cheese; the samples were sprayed twice, separated by two minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the study showed that the coating formulated with 3% roselle calyx extract/zinc oxide was able to drastically reduce mold and yeast counts (4.58 vs. 1.70 log CFU/g) and psychotropic bacteria from 3.65 to 1.08 log CFU/g at 4 months of ripening compared to the uncoated cheese. Similarly, Ríos de Benito et al [ 139 ] reinforced an edible coating based on sodium alginate/chitosan and oregano essential oil with silica particles for its application to Panela cheese. Coated cheese showed a reduction of 1.75 Log CFU/g of mesophilic aerobic bacteria compared to the untreated sample after 15 days of storage, thus improving the quality and shelf life of Panela cheese.…”
Section: Application Of Chitosan Edible Films and Coatings In Foodsmentioning
confidence: 99%